The Artificial Termination of Pregnancy: Gaps in Civil Legislation - Білоусов, Віталій Миколайович; Дробович, Тетяна Миколаївна; Мельник, Павлина Михайлівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The problem of artificial termination of pregnancy can be considered from different positions, i.e. from position of the right to life, from position of the men’s and women’s right to plan a family, from position of the right to health protection and from feminist position – the woman’s right to dispose her body. Therefore, it is necessary to outline the legal problem of artificial termination of pregnancy from the position of the right to life. This idea originates from the concept of natural human rights which are the basis for all other rights. The problems of legal regulation of the right to perform an operation of artificial termination of pregnancy are actively researched by such native and foreign jurists: N. B. Bolotina, Z. V. Romovska, O. V. Tihomyrov, M. M. Maleyina, I. I. Gorelyk, T. Gurska. Statement that a woman has the right to dispose her body concerning the life of an unborn child is unfounded. In this case there is no natural contraposition of the right to life and the right to choose. In the most cases a woman deliberately enters into sexual contact with a man and she like the man has the right to choose: or to use contraceptives or sterilization, or refuse them. The women’s position that “it is my body and I do with it what I want” contrasts with the right to life which is a fundamental principle of all other rights, so it is abuse of their right. Thus, taking into consideration the above mentioned and to somehow reduce the quantity of artificial cases of termination of pregnancy, the effective part 6 of article 281 of the Civil Code of Ukraine should be formulated as follows: “The artificial termination of pregnancy if it does not exceed twelve weeks may be done in the following cases: - if a person is under 14 years old; - if the pregnancy is a result of rape; - if the pregnant woman is HIV-positive. In the cases determined by the laws the artificial termination of pregnancy can be made from twelve to twenty two weeks of pregnancy. The list of circumstances which allow termination of pregnancy after twelve weeks of pregnancy is established by the laws. Thus, the groundless artificial termination of pregnancy should be forbidden on legislative level.